2015
DOI: 10.4172/2375-4494.1000219
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Heights and Visual Height Intolerance in Children 8–10 Years Old

Abstract: Objective: To evaluate the prevalence, symptoms, spontaneous course, and behavioral consequences of visual height intolerance in children in comparison to adults. Methods:Survey in three primary schools on the frequency of visual height intolerance in 455 children aged 8 to 10 years. Individual structured interviews of 90 susceptible children and 54 of their parents. Results:The prevalence of visual height intolerance in children amounted to 34%; there was no gender preponderance. The condition began at a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(76 reference statements)
0
4
0
1
Order By: Relevance
“…Epidemiological studies on children are available for anxiety disorders and specific phobias, especially fear of the dark, spider phobia, and medical phobias as well as for fear of heights, however, without detailed specification of its prevalence [37][38][39]. A survey among prepubertal children aged 8-10 years on the frequency and phenomenology of visual height intolerance and fear of heights revealed a prevalence of 34% with no gender preponderance [40]. The mean age at onset of symptoms was 5.9 years.…”
Section: Special Features Of Visual Height Intolerance In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Epidemiological studies on children are available for anxiety disorders and specific phobias, especially fear of the dark, spider phobia, and medical phobias as well as for fear of heights, however, without detailed specification of its prevalence [37][38][39]. A survey among prepubertal children aged 8-10 years on the frequency and phenomenology of visual height intolerance and fear of heights revealed a prevalence of 34% with no gender preponderance [40]. The mean age at onset of symptoms was 5.9 years.…”
Section: Special Features Of Visual Height Intolerance In Childrenmentioning
confidence: 99%
“…An essential difference of visual height intolerance in childhood is the good prognosis with spontaneous remission in up to 48% until the age of 10. Since corresponding epidemiological studies in adults found only 4.5% of individuals who reported an emergence of symptoms when exposed to heights during their first decade of life [22], it can be hypothesized that two separate courses of the development of susceptibility may exist: an early beginning visual height intolerance that usually resolves spontaneously in contrast to a, in most cases, persistent form that occurs during adulthood [23,40]. Fearrelated to height stimuli can be assumed to be a protective mechanism that restrains children from potentially harmful situations, with which they are yet too immature to cope.…”
Section: Special Features Of Visual Height Intolerance In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that untreated vHI in adults is mostly a chronic, more or less distressing disability. This does not hold for prepubertal primary school children aged 8–10 years who also showed a prevalence of vHI of about one-third (20). However, in contrast to the adult-onset type of the condition, vHI in children appears to take a benign spontaneous course.…”
Section: Discussionmentioning
confidence: 92%
“…Eine visuelle Höhenintoleranz findet sich nicht nur bei Erwachsenen, sondern auch bei Kindern; im Grundschulalter von 8 bis 10 Jahren zeigte sich eine Häufigkeit von 34%, ohne Geschlechtsunterschiede. Im Gegensatz zu Erwachsenen nimmt der Höhenschwindel der Kindheit in den meisten Fällen einen benignen Verlauf mit spontaner Remission innerhalb weniger Jahre [57]. [59], die bevorzugt hirnstammnah proximal der Übergangszone vom peripheren Nerven auf das zentrale Myelin (Oligodendroglia) lokalisiert ist.…”
Section: Visuelle Höhenintoleranz/akrophobieunclassified